Distance learning techniques and technologies for effective and successful online learning - Kauk , V.; Grebenyuk , V.; Pugolovok , K.; Vodyanytskyi , D. (New Collegium, 2020)
The experience of Kharkiv National University of Radio Electronics in the transition to distance learning during the introduction of quarantine is presented. Technological and pedagogical methods for providing modern dynamic technical education in the conditions of a remote mode of work are discussed. Attention is paid to the ways of interaction with teachers and students. The opinion of students — consumers of educational technologies, on innovative teaching methods is given. Features of fast transition from usual academic training to completely distance or blended learning are considered. The most significant difficulties and obstacles in organizing such training are given. Challenges that impose additional requirements during quarantine to ensure the quality of education have been identified. Statistics on the real growth of the load on the distance learning system and how to overcome technological difficulties are presented. When working with server technologies, attention is paid to the process of deployment and constant updating of the virtual machine on external hosting. The factors that directly affect the quality of the system as a whole are given. Recommendations for operating the system during heavy loads are given. The tasks that are a priority for the first stage of the transition to blended learning have been identified. Emphasis is placed on the positive results obtained during quarantine in distance learning, and has prospects for further operation of the distance learning system. Among the modern challenges to higher education are the following: constant quality control of the educational process, student-centered learning, academic integrity, raising ratings, breaking outdated stereotypes, increasing motivation to master modern information technology in teachers. Technological, pedagogical and organizational directions of distance learning system development at the university are clearly defined.